TRANSFORMATION OF NATURE VALUES IN THE CONTEXT OF GLOBALIZATION - Kistaubaev Savlabek Usmanovich (Ethiopian International Journal of Multidisciplinary Research, 2025)
The article analyzes how national values associated with nature, as a specific component of the culture of society , were formed as a result of the need to strengthen and transform a conscious, responsible attitude of man to nature. The principles of humanism in rituals, love for nature and the ability to learn lessons from it must be instilled today in the psyche, consciousness and worldview of each person.